Construction, pattern recognition and performance of the CLEO IIILiF-TEA RICH detector - Artuso, M; Ayad, R; Bukin, K; Efimov, A; Boulahouache, C; Dambasuren, E; Kopp, S; Mountain, R; Majumder, G; Schuh, S; Skwarnicki, T; Stone, S; et al. (2003)
We briefly describe the construction and performance of the LiF-TEA RICH detector constructed for the CLEO III experiment. (C) 2003 Elsevier Science B.V. All rights reserved.